Foundations for assessing the water footprint of food loss and waste - Brown, Samuel P. (Kansas State University, 2021)
Food production has made an indelible environmental impact on the landscape of the United States, accounting for nearly three-fourths of the nation’s water consumption, 55% of its land use, and a significant amount of energy utilization along the food supply chain (FSC). Yet, much of this resource use does not serve a beneficial purpose - over 33% of the U.S. food supply is lost or wasted between farm and fork. This food loss and waste (FLW) is the largest contributor to municipal solid waste, accounting for 22% of waste in landfills in the U.S. Water scarcity has been identified as a pervasive threat to global society and is expected to intensify with the changing climate and growing population. To our knowledge, no studies have quantified FLW at the county level. We aim to provide the framework which will be used to assess the water footprint of FLW at a county level spatial resolution on the temporal scale of 1997 through 2017 to determine loss rates, loss quantities, and the associated water footprint increases over time in a future study. The purpose of this article will be to determine county level data for FLW rates, quantities, and variations over the aforementioned timescale. Results of this study are anticipated to aid in the determination and targeting of FLW hotspots for reduction efforts.
Keywords: Food loss and waste; Water scarcity; Food supply chain; Environmental footprint; Food; Waste